(untitled) (South East Asia Journal of Public Health, 2016)
Sexually Transmitted Infections/Reproductive Tract Infections (STIs/RTIs) are a major public health problem and a leading cause of morbidity among men and women in developing countries. The aim of the study is to explore treatment seeking behavior among the married women of reproductive age presented with symptoms of STI/RTI. A hospital-based observational study was carried out at the STI/RTI Clinic of Urban Health Centre, Shivaji Nagar, Govandi, Mumbai, India. The study involved a total of 273 married females who attended clinic for their symptoms during January to March 2012. Patients were interviewed using a pretested questionnaire to explore the detail of the treatment seeking behavior regarding STIs/RTIs. Out of total women who participated in the study, only 47.6% of the women with STIs/RTIs symptoms sought health care. Among those who did not seek treatment, 58.65 % females were belonging to 21-25 years of age group. Maximum 65.6% females who were illiterate had not sought any treatment for symptoms of these diseases as compared to 65% who had taken treatment for the presented symptoms who were educated up to higher secondary and above level. 62.5% females belonging to class V had never sought treatment as compared to 100% women who were classified to class I. The poor health seeking behavior was associated with literacy and socioeconomic class of the participants. Private sector was the most favored place for taking treatment by them. Commonest reason for not seeking treatment was no female doctor at clinic. Information, Education and Communication (IEC) sessions, about STI symptoms and the benefits of treat-ment, especially targeted at women and low socioeconomic groups might be an immediately feasible measure that will help to reduce the burden of the disease. South East Asia Journal of Public Health Vol.5(2) 2015: 65-70